Применение управляющих вычислительных машин: учебное пособие для вузов - Морозевич А. Н. Анатолий Николаевич; Николаев А. В. Александр Викторович; Пашкевич А. П. Анатолий Павлович; Петровский А. А. Александр Александрович (Минск, Вышэйшая школа, 1988)
Авт. указ. на обороте тит. л.